FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP AUDIT REPORT LAG PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2008-2012 - Alvyra Nesia Indah Putri (Diponegoro Journal of Accounting, 2014)
This study aims to prove the factors that affect the audit report lag. Publication of audited financial statements is critical as useful information for stakeholders. Effect of audit report lag information to support the benefits of audited financial statements. Factors tested in this study are firm size, leverage, and auditor industry specialization. This study uses secondary data and sampling techniques using purposive sampling method with a total sample of 259 manufacturing companies listed on the Indonesian Stock Exchange (IDX) in the year 2008-2012. The statistical methods used in this study is a multiple linear regression at a significance level of 5%. The results of this study indicate that factors of company size, leverage, and auditor industry specialization significant effect on audit report lag.